The role of glycosylated mucins in maintaining intestinal homeostasis and gut health - Hao Cheng; Hao Li; Zhong Li; Yun Wang; Liangguo Liu; Jing Wang; Xiaokang Ma; Bie Tan (Animal Nutrition, 2025)
The intestinal mucus barrier is a crucial component of the host's innate defense system, playing a vital role in regulating intestinal microecology and maintaining intestinal homeostasis. Glycosylated mucins, the core components of this barrier, are essential for preserving its integrity by preventing bacterial degradation. Additionally, mucins significantly contribute to establishing a balanced symbiotic relationship between the host and microbes. These mucins have the potential to mitigate intestinal epithelial damage by capturing and transporting cell debris and pathogenic bacteria. Meanwhile, certain bacteria help maintain the equilibrium and stability of the gut microbiome by degrading glycosylated mucins to utilize the carbohydrate chains, thus affecting the cytokine expression to regulate the synthesis and secretion of specific glycans. Investigating the complex connections between the mucus barrier and mucin glycosylation holds great promise for advancing our understanding of gastrointestinal disease mechanisms, paving the way for innovative prevention and treatment strategies.